Puss in boots - Patchett, Fiona (Usborne Books UK, 2011)
Eight titles in the popular "First Reading" series are re-issued with hardback covers with audio CDs inserted into a wallet inside the back cover, making this book and CD easy to store together. "The Young Reading" series is developed with reading expert Alison Kelly from Roehampton University to help young readers grow in confidence and ability.